Implementasi Manajemen Sumber Daya Manusia dalam Meningkatkan Kualitas Layanan Pendidikan di SDIT Ash-Shiddiiqi - Era Maya Sofa; K A Rahman; Masbirorotni Masbirorotni (Journal Of Administration and Educational Management (ALIGNMENT), 2023)
This research aims the process of implementing HR management improves the quality of educational services at SDIT Ash-Shiddiiqi. This research uses a qualitative approach method. The data collection technique used to obtain valid data is through observation, interviews and documentation taken directly from informants, namely the principal and teachers of SDIT Ash-Shiddiiqi. The data analysis techniques used are through data reduction, data presentation and drawing conclusions and verification. The results of this research are that the implementation of management in improving the quality of education is going well and is quite adequate, the implementation of HR management goes through several stages : carrying out an effective human resource planning process, carry out external recruitment through the education office and internal recruitment and selection for additional staff such as honorary teachers, placing employees according to interests and talents, holding training so that the skills of teachers and employees increase, carrying out performance assessments within one semester, provide appreciation in the form of compensation and bonuses according to position and qualifications, terminate employment relations in accordance with mutual agreement. In conclusion, "implementation of human resource management at SDIT Ash Shiddiiqi, Jambi city has improved the quality of educational services. Keywords: Human Resource Management and Education Quality Keywords: Human Resource Management and Education Quality